Negotiating marginality: towards an understanding of diverse development pathways of ethnic minorities in Vietnam - Hiwasaki, L.; Minh, Thai Thi (Wiley, 2022)
Existing studies on socio-economic differentiation in Vietnam focus on the inequality between the ethnic majority and minorities while neglecting the disparities among ethnic minorities. Using a framework to analyse marginalisation at different scales, we identified through an extensive literature review the diverse ways in which ethnic groups develop strategies to transform or maintain their marginality. These strategies depend on, at the same time influence, inequalities that manifest in processes of social differentiations and power relations. Elucidating these processes of inequalities enables us to promote livelihood opportunities that support the diverse development pathways of different ethnic groups, thus increasing the relevance of development interventions.